Improving Student Interests and learning outcomes for English Subject by using Mind Mapping through Online Zoom Application - Ika Sari Puspita (General English Education, 2023)
This study aims to Improve Interest and Learning Outcomes in English Using the Mind Mapping Method assisted by the Zoom Meeting Application in Class X IPS 2 SMA Negeri 3 Pangkalan Bun. This is a class action research (PTK) study to create better English learning. This PTK uses the Arikunto stage. Each cycle consists of four stages, namely: (1) the action planning stage, (2) the action implementation stage, (3) the observation and inner achievement stage, and (4) the analysis and reflection stage. The research subject consisted of 32 students. Research Instruments use student learning outcomes. Data Analysis uses percentage techniques. The results showed that students’ English learning outcomes increased, namely from the first cycle of 32 students of Class X IPS 2 SMAN 3 Pangkalan Bun, there were 23 students, or 72%, who had achieved a KKM score of 73 with an average class score of 75.15. In cycle II, of the 32 students of Class X IPS 2 SMAN 3 Pangkalan Bun, 30 students, or 94%, had achieved a KKM score of 73 with an average score of 81.87. Based on the actions taken, it can be concluded that the Mind Mapping Method assisted by the Zoom Meeting Application can improve the quality of the English learning process.